Internal orientation in the growth of Born-Globals. Learning from inside - Rastrollo-Horrillo, María Ángeles; Martín-Armario, Julia (My University, 2018)
Based on a longitudinal case study in a young BG by means of action-research, that allows the participation of all employees in the co-creation of internal knowledge, we identify organisational dysfunctions during the early phase that affect the development of entrepreneurial and market orientation. Using the Socio-Economic Approach to Management (Savall, 1974), we propose that the entrepreneurs need to adopt an Internal Orientation (aiming at developing a cohesive organisation), and that the ‘right time’ for doing so is not after a few years, as the literature suggests, but much earlier.
Este paper ha recibido dos premios en el congreso: 1. Thomson South-Western Award OUTSTANDING RESEARCH-BASED PAPER ON MANAGEMENT CONSULTING 2. FINALIST CAROLYN DEXTER AWARD FOR BEST INTERNATIONAL PAPER
Keywords: Organización de la empresa; Born Global (BG); Socio-Economic Approach to Management (SEAM); Internal Orientation; Dysfunctions; Growth; Resources and Capabilities